1956
DOI: 10.1302/0301-620x.38b1.83
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Infraction of the Middle of the Tibia in Ballet Dancers

Abstract: 1. A defect of the middle of one tibial crest is described in young healthy ballet dancers. 2. The clinical and radiological characteristics have been studied in four cases, and the histological appearances in two. 3. The defect is concluded to be an incomplete fatigue fracture—a fatigue infraction. 4. A fifth, uncertain, case has been added tentatively, as presenting a possible serious complication, namely acute fracture from muscle action. 5. The diagnosis, treatment and prognosis are mentioned, with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(42 citation statements)
references
References 0 publications
0
42
0
Order By: Relevance
“…Although stress fractures of the tibia are the most frequent, anterior tibia cortex consists a less common location for this type of fractures. They were fi rst described in 1956 by Burrows [1]. It is relatively rare form of stress fracture, making up 2.7% [5] to 4.6% [6] of all cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although stress fractures of the tibia are the most frequent, anterior tibia cortex consists a less common location for this type of fractures. They were fi rst described in 1956 by Burrows [1]. It is relatively rare form of stress fracture, making up 2.7% [5] to 4.6% [6] of all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although stress fractures of the tibia are the most frequent, anterior tibia cortex consists a less common location for this type of fractures. They were fi rst described in 1956 by Burrows [1], who reported on fi ve ballet dancers who had such lesion. Constant tension from posterior muscle forces and hypovascularity of the anterior aspect of the tibia predispose this site to nonunion or delayed union.…”
Section: Introductionmentioning
confidence: 99%
“…Stress fractures of the midanterior cortex are much less frequent (Burrows 1956, Devas 1975, Orava et al 1978, Orava and Hulkko 1984, Green et al 1985, Blank 1987, Barrick and Jackson 1992, Chang and Hams 1996. Milgrom et al (1985) reported a case of multiple stress fractures in a soldier where 2 stress fractures were observed simultaneously in the same tibia.…”
Section: Discussionmentioning
confidence: 99%
“…As the replacement bone matrix is formed, it takes time for the new bone to fully mineralize, and the bone is in a weakened state. As a result, strains are higher in these weak areas and as a consequence more microdamage may form (140). Individual microcracks do not decrease the elastic modulus of bone (108), but the coalescence of microdamage creates larger cracks.…”
Section: Stress Fracture Pathophysiologymentioning
confidence: 99%